2022
DOI: 10.1371/journal.pone.0252248
|View full text |Cite
|
Sign up to set email alerts
|

Water quality assessment in mosquito breeding habitats based on dissolved organic matter and chlorophyll measurements by laser-induced fluorescence spectroscopy

Abstract: Rapid urbanization and its associated pollution can affect water quality in mosquito breeding habitats and, as a result, the ecology and control of mosquito vectors. To understand the effects of pollution on mosquito vectors, an accurate assessment of water quality in breeding habitats is needed. Presently, water quality assessment of mosquito breeding habitats is usually based on the measurement of individual physicochemical parameters. However, several parameters are sometimes difficult to interpret or may n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…This could be due to the presence of algae matter which acts as food for the immature to support their growth. This is consistent with other studies that observed that algae was used as food for mosquito larvae [73][74][75][76].…”
Section: Plos Onesupporting
confidence: 93%
“…This could be due to the presence of algae matter which acts as food for the immature to support their growth. This is consistent with other studies that observed that algae was used as food for mosquito larvae [73][74][75][76].…”
Section: Plos Onesupporting
confidence: 93%
“…This aligns with previous reports (22) identifying similar breeding sites like puddles, ditches, and shrubs in rural areas. Notably, the water in these Culex breeding sites was often polluted with organic compounds and complex mixtures (24).…”
Section: Discussionmentioning
confidence: 99%
“…It could be expected that chemical parameters would change continuously, resulting in the observed variability; therefore, the association of ecophysicochemical parameters and larval number may also change. All sites surveyed are located in or near disturbed areas, where changes in water quality due to organic and nutrient pollution can affect the replacement of native mosquito species or their adaptation to polluted breeding habitats (Huzortey et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…All sites surveyed are located in or near disturbed areas, where changes in water quality due to organic and nutrient pollution can affect the replacement of native mosquito species or their adaptation to polluted breeding habitats (Huzortey et al. 2022).…”
Section: Discussionmentioning
confidence: 99%